2011
DOI: 10.4141/cjss10005
|View full text |Cite
|
Sign up to set email alerts
|

Context for re-evaluating agricultural source phosphorus loadings to the Great Lakes

Abstract: Joosse, P. J. and Baker, D. B. 2011. Context for re-evaluating agricultural source phosphorus loadings to the Great Lakes. Can. J. Soil Sci. 91: 317–327. Over the past decade, scientists have been discussing the re-emergence of harmful algal blooms and excessive growth of Cladophora in some areas of the Great Lakes. An observation that has emerged from these discussions is that management of non-point or diffuse sources of phosphorus will be more important in the future in order to address symptoms of eutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 20 publications
1
51
0
Order By: Relevance
“…However, in recent years P losses from agricultural fields in the Western Lake Erie Basin (WLEB) have been identified as a primary contributor to resurgent harmful and nuisance algal blooms (HNABs) in Lake Erie (Chaffin et al 2011). While there has not been any significant change in TP loading since the mid-1990s, there has been an increase in soluble P (SP) loading during this period (Joose and Baker 2011). This period coincides with "peak" adoption of no-till in this watershed.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…However, in recent years P losses from agricultural fields in the Western Lake Erie Basin (WLEB) have been identified as a primary contributor to resurgent harmful and nuisance algal blooms (HNABs) in Lake Erie (Chaffin et al 2011). While there has not been any significant change in TP loading since the mid-1990s, there has been an increase in soluble P (SP) loading during this period (Joose and Baker 2011). This period coincides with "peak" adoption of no-till in this watershed.…”
mentioning
confidence: 89%
“…2011). While there has not been any significant change in TP loading since the mid-1990s, there has been an increase in soluble P (SP) loading during this period (Joose and Baker 2011). This period coincides with "peak" adoption of no-till in this watershed.…”
mentioning
confidence: 95%
“…T he need to reduce nutrient loads from agricultural watersheds poses a daunting challenge, considering the continental scale of water quality problems in the Gulf of Mexico (Turner et al 2008), Great Lakes (Joose and Baker 2010), and Chesapeake Bay (Russell et al 2008). Strategies to address nutrient reduction have suggested that a mix of practices will be required across multiple landscape positions to achieve water quality goals (Iowa Nutrient Reduction Strategy Science Team 2012).…”
Section: Featurementioning
confidence: 99%
“…There is concern, however, that the extent of conservation tillage has peaked and that there is now more tillage and bare soil exposed over winter than in the past (A. Hayes, Ontario Ministry of Agriculture, Food and Rural Affairs [OMAFRA] personal communication; Statistics Canada 2016). Such practices are of even greater importance in southwestern Ontario, an area where agricultural practices, including tillage practices, have an effect on Great Lakes water quality (Joosse and Baker 2011;Molder et al 2015). The amount of crop residue left in the field after harvest is important for soil and water storage (Daughtry and Hunt Jr. 2008), erosion control (Kumar and Goh 1999;Mailapalli et al 2013;Enciso et al 2014), and assessment and modeling of soil carbon (C) sequestration (Aguilar et al 2012a).…”
mentioning
confidence: 99%